2006
DOI: 10.1007/s11104-006-9136-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of elemental allelopathy in Acroptilon repens (L.) DC. (Russian Knapweed)

Abstract: Although Acroptilon repens (L.) DC. (Russian knapweed) is known to concentrate zinc (Zn) in upper soil layers, the question of whether the elevated Zn has an allelopathic effect on restoration species has not been addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In both cases, the effect has been reported on species of phytoplankton. Although phytoplankton vary from vascular plants in some aspects, they function similarly both physiologically and ecologically (Morris 1980). Wium-Andersen et al (1982) clearly demonstrated the effect of elemental S on the photosynthesis of a species of epiphytic phytoplankton, however, as is often the case, the concentrations of S used in the experiments did not necessarily represent levels found in nature.…”
Section: Sulfurmentioning
confidence: 92%
See 4 more Smart Citations
“…In both cases, the effect has been reported on species of phytoplankton. Although phytoplankton vary from vascular plants in some aspects, they function similarly both physiologically and ecologically (Morris 1980). Wium-Andersen et al (1982) clearly demonstrated the effect of elemental S on the photosynthesis of a species of epiphytic phytoplankton, however, as is often the case, the concentrations of S used in the experiments did not necessarily represent levels found in nature.…”
Section: Sulfurmentioning
confidence: 92%
“…Isolate and characterize toxin Vivrette and Muller (1977), Morris et al (2006) Determine toxin levels found naturally in accumulator species, rates of deposition, and accumulation in soils Sharma and Tongway (1973), Vivrette and Muller (1977), Boyd et al (1999), Boyd and Jaffre (2001), Zhang et al (2005Zhang et al ( , 2007 Select proper bioassay based on Vivrette and Muller (1977), Lesica and Deluca (2004), Morris et al (2006) growth form species phenology Determine uptake and symptoms of the toxin in affected species Vivrette and Muller (1977), Morris et al (2006) Source: Adapted from Fuerst and Putnam (1983) Plant Ecol (2009) 202:1-11 5 which concentrate their roots at the soil surface, may be better candidates. For species which are thought to phytoenrich elements through acidification or other modifications of the rhizosphere, root architecture may not be as important.…”
Section: Criteria For Determining Elemental Allelopathymentioning
confidence: 99%
See 3 more Smart Citations